Size dependency of spatial and temporal patterns of marine migration of sea trout (Salmo trutta L.) and Arctic char (Salvelinus alpinus (L.)) in Repparfjord Northern Norway - Ulvund, John Birger (Institutt for biologi, 2011)
Acoustic telemetry was used to study the movements and habitat use of sea trout (Salmo trutta L.) and Arctic char (Salvelinus alpinus (L.)) in Repparfjord in Northern Norway during July until October 2010. In total, 18 trout and 8 char was internally tagged with acoustic depth temperature-tags (ADTT), and 6 trout and 3 char with identification-tags. Detected fish ranged in size with an average (mean±SE) of 27.8±1.6 cm for trout and 29.1±1.8 cm for char. All fish was monitored by 32 stationary hydrophones placed in zones over the fjord system during the whole time period in addition to manual tracking. Concerning temporal aspects results indicated that trout ascend earlier than char, contradicting other findings in areas close to the study area. However, no statistical analysis were carried out due to all fish were captured at sea so no descend time was recorded. Concerning spatial usage data showed results on distance to land and temperature preferences with fish length. However, species had a trend on distance to land and temperature, where char was observed closer to shore and in colder waters. Concerning zone there was a significant difference in spatial habitat usage on interaction between fish length and species as well as on species. There was a trend with a negative relationship on fish length and zone usage for char indicating that smaller fish seek further out in the system in addition to differences between species where trout occupied inner areas and char was detected more often in the outer areas of the system. This is in accordance with earlier studies that states species will exploit different areas of the system. Data collected from the ADTT-tags showed that trout on average preferred slightly warmer (0.7°C warmer) and shallower water (0.59 m. vs. 0.75 m.) than char. However, the only significant here was on temperature with a positive relationship over fish length.